Legal Review on the Transfer of Land Rights (Buying and Selling) to Minors - Yusup Abaidata (Estudiante Law Journal, 2021)
Abstract:This study aims to determinelegal review of the transfer of land rights (sale and purchase) to minors.The research method used by the author in this study is normative research. The research approach uses analytical descriptive and uses qualitative analysis techniques. The results of this study showThe process of transferring rights to the owner or seller of underage land must basically meet the conditions for buying and selling land, where the conditions are material and formal. The material requirement is that the land to be traded is the land owned by the seller and the land is not in dispute. While the formal requirements are related to the administration and the deed of sale and purchase of land. So, legally minors in terms of the process of buying and selling land are basically not and are not regulated in the laws in force in Indonesia, unless the minor has a companion or in this case is his guardian, so that the process of land transfer or the process of buying and selling land This can be done by a child who is still under age through his guardian according to a court order.